2020
DOI: 10.1002/qua.26166
|View full text |Cite
|
Sign up to set email alerts
|

Ternary chalcogenides XGaS2 (X = Ag or Cu) for photocatalytic hydrogen generation from water splitting under irradiation of visible light

Abstract: Ternary chalcogenide silver gallium sulfide (AgGaS2), which has an orthorhombic structure, was already synthesized. However, the feasibility of using the crystal for hydrogen production through photocatalytic water splitting has not been explored. Here, we systematically investigated the structural, electronic, optical, and transport properties of XGaS2 (X = Ag or Cu) with orthorhombic structure by using the first principles calculations. The band alignments indicate that all calculated absolute potentials of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Recently, Liu et al have calculated the carrier mobility of orthorhombic and tetragonal XGaS 2 ( X = Ag, Cu) based on the deformation potential (DP) theory proposed by Bardeen and Shockley. 36 The results show that the tetragonal phase presents higher electron and hole mobility than the orthorhombic phase. In addition, Park et al have observed the chalcopyrite (tetragonal) AgInS 2 revealing longer lifetimes than the orthorhombic phase, which can be associated with the enhanced charge transfer.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, Liu et al have calculated the carrier mobility of orthorhombic and tetragonal XGaS 2 ( X = Ag, Cu) based on the deformation potential (DP) theory proposed by Bardeen and Shockley. 36 The results show that the tetragonal phase presents higher electron and hole mobility than the orthorhombic phase. In addition, Park et al have observed the chalcopyrite (tetragonal) AgInS 2 revealing longer lifetimes than the orthorhombic phase, which can be associated with the enhanced charge transfer.…”
Section: Resultsmentioning
confidence: 95%
“…TMDCs of groups IV–VI in 0D, 1D, 2D, and 3D morphology such as MoS 2 , WS 2 , TiS 2 , MoSe 2 , and WSe 2 have been extensively explored due to their excellent optical, electronic, and catalytic activities (unusual catalytic activity at the edges), crystalline structure, layer dependent metal to insulator transition, etc. Cadmium sulfide (CdS), the most investigated chalcogenide with a low band gap (∼2.42 eV) and excellent electronic mobility, suffers from the drawback of extreme photocorrosion. To stabilize and modify the optical properties, a solid solution and homojunction of CdS with ZnS with a fractional composition (Cd (1– x ) Zn x S) have been reported. , Ternary and multinary chalcogenides such as I-III-VI 2 , I 2 -II-IV-VI 4 , Cu 2 MoS 4 , Cu 2 MoSe 4 , Cu 2 WS 4 , AgGaS 2 , LiAlS 2 , LiGaSe 2 , Cu 2 FeSnS 4 , Cu 2 NiSnS 4 , Cu 2 ZnSnS 4 , and Dy 4 S 4 Te 3 prevail upon binary TMDCs because of their tunability, choice of several atomic combinations, suitable band gap, and easy fabrication via solution processing/hydrothermal/solid-state synthesis in the 2D structures. …”
Section: Carbon Nitride–chalcogenide 2d/2d Vdw Structuresmentioning
confidence: 99%
“…This underlines the notion that the local polarization in the xy -plane also plays an important role in charge carrier migration. Previous studies on compounds belonging to the same space group ( Pna 2 1 ), such as AgGaS 2 and CuGaS 2 , have reported electron mobilities as high as 271.2 and 355.3 cm 2 s –1 V –1 , respectively, with hole mobility only reaching an order of magnitude of 10 2 cm 2 s –1 V –1 . For the template β-CuGaO 2 , despite bulk polarization exceeding 80 μC/cm 2 in the z -direction, research has confirmed that μ h and μ e along [001] are only 1691.45 and 147,851.6 cm 2 s –1 V –1 , respectively .…”
Section: Resultsmentioning
confidence: 99%